Frequency of Multi Drug Resistant E.coli Urinary Tract Infection Presenting to a Tertiary Care Hospital. - Jauhar, Maliha; Abbas, Ghulam (Pakistan Journal of Kidney Diseases, 2024)
Background: Urinary tract infections (UTIs) are a severe public health problem and are caused by a range of pathogens, but most commonly by gram negative and gram positive organisms. High recurrence rates greatly increase the economic burden. This study was conducted to determine the frequency of multidrug resistant Escherichia Coli in patients with urinary tract infections. Methods: Descriptive cross sectional study was conducted over 6 months among 146 patients presenting with E.Coli UTI. Urine culture and sensitivity was performed from the same laboratory and reported by a consultant microbiologist. Results: Among the 146 patients, 65 (44.5 %) were male patients while 81 (55.5 %) were female patients. Mean age of our study cases was 46.87 ± 8.70 years. Of these 146 study cases, 90 (61.6 %) belonged to rural areas and 56 (38.4 %) belonged to urban areas. Diabetes was present in 31 (21.2 %), hypertension was present in 54 (37.0 %) and 27 (18.5 %) had chronic kidney disease. Mean body mass index was 26.23 ± 1.99 kg/m2 and obesity was present in 27 (18.5 %). Mean disease duration was 3.43 ± 1.57 days and 90 (61.6 %) had duration of illness up to 3 days. Multi - drug resistant E. coli was noted in 69 (47.3%). Conclusion; Almost half of our patients had MDR E.coli UTI and was significantly associated with increasing age, residential status, diabetes, hypertension, disease duration and obesity. Urine cultures are recommended to identify MDR in our community.